FROM CRISIS TO KAIROS (Hekima Review, 2006)
In trying to understand the community called Church in Africa today contemporary ecclesiology presents a fundamental flaw: it neglects the social context. A theological reflection based solely on scripture and tradition without a contextual consciousness cannot give a completely valid and true image of the church in Africa. Orobator parts ways with the current trend by undertaking a theological analysis based on a critical appraisal of the church’s experience, praxis and activities.